STRATEGI PEMASARAN PAKET WISATA FULL DAY DI PT. TOUR EAST INDONESIA - Putu Geni Jaya Ksamawan; I Made Kusuma Negara; I Putu Sudana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2014)
he development of increasing tourist arrivals to Bali led to the development of business and tourism in the world of business, one business trip in Bali. PT. Tour East Tours and Travel is the one of the travel agents in Bali in this to win the competition with other companies, the need for proper marketing strategy and correct. This study aims to determine the marketing strategy Full Day tour packages PT. Tour East Indonesia and what strategies can be implemented in the PT. Tour East Tours and Travel to boost sales of tour packages to tourists as well as winning the competition with other companies. In this study using Qualitative descriptive data analysis techniques combined with a SWOT analysis to figure out what the right strategy is used to market tour packages Full Day of PT. Tour East Indonesia. Based on the SWOT matrix analysis obtained a marketing strategy that can be applied to PT. Tour East Tours and Travel is a strategy creation and development of tourism products, increased promotion strategies, human resource development strategy, market segmentation strategy development, and strategies for improving the quality of products and services. From the results of this study can be given advice to the PT. Tour East Tours and Travel is improving service process management and define market segments and maintain the image of the internal and external environment, while maintaining a cooperative relationship, and held training to staff meetings.